CSF Neurofilament Light Chain Concentrations Predict Outcome in Bacterial Meningitis. Issue 1 (January 2022) - Chekrouni, Nora; van Soest, Thijs M.; Brouwer, Matthijs C.; Willemse, Eline A.J.; Teunissen, Charlotte E.; van de Beek, Diederik
Abstract : Background and Objectives: Neurofilament light chain (NfL) is a biomarker for neuroaxonal damage and has been found to be elevated proportionally to the degree of neuronal damage in neurologic diseases. The objective of this study was to determine the prognostic accuracy of NfL concentrations on unfavorable outcome in adults with community-acquired bacterial meningitis. Methods: We measured NfL concentration CSF samples from a prospective cohort study of adults with community-acquired bacterial meningitis in The Netherlands and determined associations between NfL CSF concentrations, clinical characteristics, and outcome in multivariate analyses. We identified independent predictors of an unfavorable outcome (Glasgow Outcome Scale scores 1–4) by logistic regression. Results: CSF NfL concentrations were evaluated in 429 episodes of 425 patients with community-acquired bacterial meningitis. The median age of 429 episodes was 62 years (interquartile range, 50–69 years). Of note, 290 of 422 (68%) episodes presented with an altered mental status (Glasgow Coma Scale score < 14). Most common causative pathogens were Streptococcus pneumoniae (73%), Neisseria meningitidis (7%), and Listeria monocytogenes (5%). The overall case fatality rate was 62 of 429 (15%), and unfavorable outcome occurred in 57 (37%) of 429 episodes. In multivariate analysis, predictors of unfavorable outcome were older age (OR 1.03, 95% CI 1.01–1.05), cranial nerve palsy (OR 4, 95% CI 1.6–10.3), high serum C-reactive protein concentration (OR 1.3, 95% CI 1.01–1.05), and high CSF NfL concentration (OR 1.5, 95% CI 1.07–2.00). CSF NfL concentrations were higher in patients presenting with focal cerebral deficits (717 pg/mL [416–1, 401] vs 412 pg/mL [278–731]; p < 0.001). The area under the curve (AUC) for predicting unfavorable outcome in bacterial meningitis of CSF NfL concentration was 0.69 (95% CI, 0.64–0.74). Discussion: CSF NfL concentration is independently associated with unfavorable outcome in adults with community-acquired bacterial meningitis, suggesting that CSF NfL concentration may be a useful biomarker for prognostic assessment in bacterial meningitis. Classification of Evidence: Can the level of NfL in CSF (the index test) predict unfavorable outcome in patients with bacterial meningitis, in a cohort of bacterial meningitis patients with a favorable and unfavorable outcome? This study provides Class II evidence that NfL level in CSF is a moderate predictor, with the AUC for predicting unfavorable outcome in bacterial meningitis being 0.69 (95% CI, 0.64–0.74).